Effectiveness of Professional Zakat Collection Strategies at the National Board of Zakat Institutions (BAZNAS) Jember Regency - Jasmine, Encik Dalilah; Mustafidah, Ayyu Ainin (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This study aims to describe the professional zakat collection strategies implemented by BAZNAS Jember and evaluate their effectiveness in enhancing muzakki participation and institutional performance. Method: A qualitative descriptive approach was employed. Data were collected through observation, semi-structured interviews with BAZNAS officials and muzakki, and documentation. Data analysis followed the interactive model of Miles and Huberman, including data reduction, presentation, and conclusion drawing. Credibility was ensured through source triangulation. Practical Applications: The findings suggest that socialization and media-based promotion strategies can optimize professional zakat collection. The implementation of UPZ units in government institutions and digital tools like QRIS and social media campaigns can be replicated to enhance transparency, convenience, and public trust in zakat management. Conclusion: BAZNAS Jember’s strategies—centered on socialization and media promotion—are effective but not yet maximal. Effectiveness is supported by efficiency, stakeholder satisfaction, and adaptability. While muzakki participation increased significantly in 2023, collection levels declined in 2024, indicating a need for more consistent and sustained efforts to maximize zakat potential.